Peptide arrays as tools for unraveling tumor microenvironments and drug discovery in oncology - Grab, Anna Luise; Reißfelder, Christoph; Nesterov-Müller, Alexander (Cells, 2026)
HighlightsWhat are the main findings?Recent achievements report on the application of peptide array technology in the study of tumor microenvironment....
Online veröffentlicht: 14. Januar 2026
Gesehen am 16.02.2026